Interplay Among Physical Characteristics Play Position and Shooting Accuracy of Elite-Female Basketballers - Olufunmilola Leah Dominic; Chioma Esther Whoba; Adetayo Ebun Talabi; Surajudeen Tosho Bakinde; Sikiru Adewale Adeoye; Tajudeen Olarewaju Ibraheem; Iliasu Yakubu Seidina (Universitas Negeri Semarang, 2018)
This study was conducted to examine effect of specialty and training frequency on physical fitness profile of Federal Capital Territory Abuja Karate Team. Descriptive correlational research design with stratified and purposive sampling was adopted to study 16 out of 30 karatekas (male, n = 9; female, n = 7); age, 28.4 ± 7.0 years. Data were collected using stopwatch, punch pad, kicking pad, karate belt, training bag and measuring tape after informed consent. SPSS 20.0 was used for data analysis with frequency, percentage, mean, t-test and multiple regression with 0.05 alpha level. No significant difference between the fitness profiles of kumite and kata and kata only group; t = .803, MD = 1.467, df = 14, p = .435 and 2 = 4% (0.04), and 95% CI = -5.38 to 2.44. Those who trained 3 days/wk. had higher fitness profile than those who trained daily, t = 2.32, MD = 3.37, df = 14, p = .039, 2 = 30% (0.30) and 95% CI = -6.54 to -0.19. Training frequency had greater influence on their fitness profile = .65, p =.01. Training frequency of 3-4 days/wk. and regular assessment of physical fitness using SKFT batteries was recommended.